Typologies of Institutional Communication - IOSIF, Gabriela (Annals of Spiru Haret University. Economic Series, 2014)
From the point of view of Durkheim, institutions are ways of acting, feeling and thinking, expressing any social act. Institutions have stringent action on the individual, have its own existence, independent of individual manifestations, which are distinctive for a given group, being accepted by all members. Types of social institutions are economic institutions, educational, political, cultural and family. Within institutions, communication is an inherent phenomenon. For Katz and Kahn "communication is a social process of great relevance to the functioning of each group, organization or society," the very essence of the social system or organization. The organizational structure provides stability for human communication and facilitates administrative tasks. (Rogers Everett M. and Agarwala-Rogers Rekha, 1976, p. 6). Therefore, an effective institutional communication adds value to any institution.